If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + y = 114 Solving X + y = 114 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1y' to each side of the equation. X + y + -1y = 114 + -1y Combine like terms: y + -1y = 0 X + 0 = 114 + -1y X = 114 + -1y Simplifying X = 114 + -1y
| 3x-5+x=-7 | | -2(x-4)+6=3 | | (7v+3v+6)+(-4v+2v+1)= | | 5(2a-4b)-4(a-5b)= | | 7x+168+4x+166=180 | | logx(27)=10 | | 9a(-7a+4)= | | 5y^4+3y^4= | | 3u-10=14 | | 4+(x-5)=2(3-x) | | 4x^2-28x+c= | | Z+20=6 | | (Xy^2)(x^2+3xy+9)=0 | | 2x^8+6x^8= | | 2(x+6)x^2=90 | | 21x^2y+2xy-8=0 | | 3(x-2)=5(2+3) | | h+h+4=218 | | y=x^5+6x+8 | | 14(y-7)+12y=16-70 | | 6+2(7x+2)=3 | | 5y=4x+12 | | -3x+3=5x-5 | | (3a+4b)(3a-4b)= | | x*1+3*1,5+(x-3)*2=19,5 | | 3x+37=97 | | x^2-4x+2=-1 | | X=15000+0.36(8600+0.2X) | | h+h+20=300 | | 3-(x-4)=4-(2x+5) | | 15-(-23)= | | 0=-x^2-9x+7 |